The Relationship Between Learning Strategy for Office Aplication With Learning Succes at LKP Widyaloka Bukittinggi - Elinur Sakiyah; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research was motivated by the low learning success in the office application training at LKP Widyaloka Bukittinggi. Researchers suspect that the cause of the training  participants' low learning success is to the lack of implementation of learning strategies by the instructors. The problems studied in this research are, "Is there a relationship between the learning strategy of office applications and the success of studying at LKP Widyaloka Bukittinggi?". This research is to see an overview of learning strategies, an overview of learning success, how the relationship between the two. This research is a correlational study using a quantitative approach. The population in the study amounted to 40 people who met the criteria. While the sample was determined to be 75% of 40, namely 30 people. Data collection in the research was conducted by researchers using a questionnaire technique and the tools used were questionnaires. The data analysis technique uses the percentage formula, the Product Moment formula. It can be concluded that: (1) the learning strategy at LKP Widyaloka Bukittinggi office applications is not good, (2) the success of learning office applications in LKP Widyaloka Bukittinggi is categorized as low. (3) there is a significant relationship between the office application learning strategy and the learning success at LKP Widyaloka Bukittinggi. For this reasons, the authors give several suggestions (1) It is hoped that the instructor in making an attractive media learning strategy method increases high learning success, so that active participants office application training activities LKP Widyaloka Bukittinggi can do well. (2) It is expected that LKP Widyaloka Bukittinggi will improve the quality of learning training for office applications at LKP Widyaloka Bukittinggi. (3) Researchers are expected to examine other variables that affect involvement citizens in learning.Keywords: learning strategies, learning success.